Fatigue behavior of a Zr-based bulk metallic glass under uniaxial tension–tension and three-point bending loading mode. (May 2015) - Yue, Y.; Wang, R.; Ma, D.Q.; Tian, J.F.; Zhang, X.Y.; Jing, Q.; Ma, M.Z.; Liu, R.P.
Abstract: The fatigue behavior of as-cast Zr41.2 Ti13.8 Cu12.5 Ni10 Be22.5 bulk metallic glass was systematically investigated under uniaxial tension–tension and three-point bending loading modes. To obtain the fatigue stress-life (S–N) diagram, stress-controlled experiments were conducted using a computer-controlled material test system electrohydraulic testing machine at 25 Hz with a 0.1 R ratio in air at room temperature. The fatigue endurance limit (630 MPa) in stress range terms under cyclic tensile load was almost three times higher than that under the three-point bending condition (225 MPa). Both fatigue resistances were similar at higher stress level. The fatigue fracture morphologies associated with the S–N curve indicated that the defects have little to no influence on the crack initiation and the fatigue life in low cycle fatigue range. However, at lower stress level, the most detrimental factor was the number of defects that resulted in fatigue endurance limit discrepancy. Highlights: The fatigue endurance limit (TT) was almost 3 times higher than that of 3 PB. The S–N curve was fitted for engineering applications. It was found that the fatigue life was mainly controlled by crack initiation. The fatigue mechanism for metallic glass was discussed.